The Employee’s Right to Resign: An Analytical Study under the Saudi Labor Law - Nerdin Abdul Mohsen Mohammed Eraqi (International Journal of Law Research and Studies, 2025)
This study aims to clarify the legal provisions governing resignation in fixed-term employment contracts under Saudi Labor Law. It explains the concept of resignation, distinguishes it from similar termination mechanisms, outlines the legal procedures for resigning, and examines the employer’s authority to respond, along with the balance between the rights of both parties. The study adopts an analytical approach, reviewing relevant statutory texts and assessing their consistency and sufficiency in regulating resignation within fixed-term contracts. The study concludes with several key findings, most notably that the legislator effectively regulated essential aspects of resignation, including the presumption of acceptance if the employer fails to respond within the statutory period. It also recognizes the legislator’s awareness of possible changes in the employee’s circumstances by permitting withdrawal of resignation within seven days, provided it has not yet been accepted. Additionally, the employer’s ability to reject a resignation without justification aligns with the legal nature of fixed-term contracts, which are presumed to continue until their agreed end. Accordingly, refusal is considered a reaffirmation of this default and requires no further explanation. The study concludes with several recommendations, including amending Paragraph (2) of Article 79 (bis) of the Labor Law so that the employment contract is deemed terminated on the date the employee becomes aware of the employer’s acceptance of the resignation, rather than the acceptance date itself, to avoid the employee unknowingly continuing to perform contractual duties. It also recommends adding a clear provision in the Executive Regulations stating that the employer may not reject a resignation based on its reasons since the employee is not required to justify it. Additionally, the study recommends allowing the employee to withdraw their resignation again if the employer postpones acceptance, where the delay renders the resignation ineffective or undermines its intended purpose.